2020
DOI: 10.1016/j.semcancer.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

The antigenic link between thyroid autoimmunity and breast cancer

Abstract: The association between breast cancer and benign thyroid disorders, in particular thyroid autoimmunity, has been debated for decades. Autoantibodies to thyroid peroxidase, the hallmark of thyroid autoimmunity, have a higher prevalence among patients with breast cancer compared with the general population. Furthermore a correlation between their positivity and a better prognosis of breast cancer was found in several independent small-scale studies, even if such observation was not confirmed in a subsequent retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 237 publications
(310 reference statements)
0
27
0
Order By: Relevance
“…In our study, peritumoral lymphovascular invasion rate was lower (17.8%), and there was no significant difference in terms of peritumoral lymphovascular invasion between the groups. Normal and neoplastic breast epithelial cells express thyroid hormone receptors and thyroid hormones show an in vitro tumor-promoting effect .In particular, they induce estrogen-like differentiation and lobular growth of breast tissue [17] .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, peritumoral lymphovascular invasion rate was lower (17.8%), and there was no significant difference in terms of peritumoral lymphovascular invasion between the groups. Normal and neoplastic breast epithelial cells express thyroid hormone receptors and thyroid hormones show an in vitro tumor-promoting effect .In particular, they induce estrogen-like differentiation and lobular growth of breast tissue [17] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liu et al have recently shown that TPOAbs level is associated with cardiometabolic risk factors in non-obese euthyroid individuals [56]. Another widely discussed issue is the connection between thyroid antibodies and cancer [57][58][59]. Some authors reported positive association between anti-thyroid autoantibodies (TgAbs and/or TPOAbs) titers and papillary thyroid cancer (PTC) risk and severity [60,61], however, others question the role of thyroid autoimmunity in thyroid cancer [62].…”
Section: Clinical Utility Of Tpoabs Testingmentioning
confidence: 99%
“…Some authors reported positive association between anti-thyroid autoantibodies (TgAbs and/or TPOAbs) titers and papillary thyroid cancer (PTC) risk and severity [60,61], however, others question the role of thyroid autoimmunity in thyroid cancer [62]. The large majority of studies reported higher frequency of thyroid antibodies, especially TPOAbs, in breast cancer patients in comparison with healthy controls [59]. Several reports showed a more favorable outcome of breast cancer in TPOAbs-positive patients than in TPO-negative patients, nevertheless the protective role of TPO-driven autoimmunity continues to be debated [59,63].…”
Section: Clinical Utility Of Tpoabs Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…T hyroid and breast tissue share some common molecular markers. Both normal and pathologic breast tissues exhibit high concentrations of sodiumiodide symporter, peroxidase, and deiodinase, indicating the active involvement of breast tissues in iodine metabolism (1,2). There is considerable conflicting literature on the relationship between thyroid and breast disorders (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%